Grado de responsabilidad y nivel de conocimiento respecto al manejo de residuos en la población de Angaraes – Huancavelica - Taipe Buendía, Reina (2022)
The purpose of this research was to determine the relationship between the degree of responsibility and level of knowledge regarding solid waste management by mothers of the neighborhood Virgen del Carmen - Angaraes - Huancavelica. The study population and sample consisted of 99 mothers living on the banks of the Sicra River. First, we made the corresponding informal visits to the place to observe how the population acts with respect to the operation of solid waste, then we applied a survey and questionnaire which was validated by Cronbach's alpha which had a value of 0.730, this value shows that the reliability of our instrument is good. Finally, the data obtained were sorted and classified using Microsoft Excel and analyzed statistical software. The results showed that 70.71% of the inhabitants have an average level of responsibility with respect to solid waste management and 79.80% of the inhabitants have an average level of knowledge with respect to solid waste management in their locality. The conclusion is that if there is a degree of responsibility and a good level of knowledge, solid waste management will improve.